2013
DOI: 10.3906/biy-1306-27
|View full text |Cite
|
Sign up to set email alerts
|

The S-genotyping of wild-grown apricots reveals only self-incompatible accessions in the Erzincan region of Turkey

Abstract: IntroductionApricots are grown in warm temperate to subtropical regions of all continents. Over a long period, cultivation moved westward from China to Middle Asia and, further, to Europe. Turkey dominates world apricot production with approximately 500,000 t of annual production. Apricot has been widely cultivated for its edible fruit throughout Turkey since ancient times, especially in Inner Anatolia (e.g., Malatya, Erzincan, Aras valley). Some parts of Turkey, especially the Erzincan plain, have huge native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…The size of the PCR products was compared with those previously published by other researchers (Vilanova et al, 2005;Halász et al, 2007Halász et al, , 2010. For S 8 and Sc alleles, although Vilanova et al (2005) and Halasz et al (2010) reported as 353 and also, Halasz et al (2013) reported as 355 bp, the hereby result obtained was 354 bp band size. These differences might be explained by the genetic analyzers that affect the sensitivity of the method (Cachi and Wünsch, 2014).…”
Section: Resultsmentioning
confidence: 43%
See 4 more Smart Citations
“…The size of the PCR products was compared with those previously published by other researchers (Vilanova et al, 2005;Halász et al, 2007Halász et al, , 2010. For S 8 and Sc alleles, although Vilanova et al (2005) and Halasz et al (2010) reported as 353 and also, Halasz et al (2013) reported as 355 bp, the hereby result obtained was 354 bp band size. These differences might be explained by the genetic analyzers that affect the sensitivity of the method (Cachi and Wünsch, 2014).…”
Section: Resultsmentioning
confidence: 43%
“…Mehlenbacher et al (1991) reported that the European group of apricot (Europe, North America, South Africa and Australia are included) may be described as self-compatible. It was reported by Halasz et al (2013) to support the S-genotype determinations, as first intron lengths were also determined for all genotypes using fluorescently labelled primers and automated sizing on a capillary sequencer. Analysis of the first intron in 63 wild-grown apricot accessions from Turkey showed that 17 of 63 apricot accessions had 355 bp fragment.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations